Waning effectiveness of CoronaVac in real life: A retrospective cohort study in health care workers. Issue 18 (20th April 2022) - Can, Gunay; Acar, Hazal Cansu; Aydin, Sumeyye Nur; Balkan, Ilker Inanc; Karaali, Ridvan; Budak, Beyhan; Saltoglu, Nese
Abstract: Background: Real-world studies showed varying levels of effectiveness of CoronaVac vaccine against COVID-19 disease. This study aimed to assess the association between the vaccination with CoronaVac and the COVID-19 infections among the health care workers in a university hospital and to determine the vaccine effectiveness against COVID-19 in a period when alpha variant was dominant. Methods: This retrospective cohort study was conducted in a university hospital in Istanbul, Turkey employs 4067 health care workers. The follow-up period was defined as starting 14 days after receiving the second dose for fully vaccinated group. Health care workers were censored when have a positive PCR test result or at the end of the study. Unvaccinated health care workers were censored if they receive any COVID-19 vaccine doses. The incidence rate ratio and Cox regression were used to estimate the unadjusted and adjusted effectiveness of the vaccine. Findings: Seventy-one percent of the health care workers were fully vaccinated whereas 29% percent did not receive any doses. The incidence rate of SARS-CoV-2 infection was 133.7 vs 70.7 per 100.000 person-days in the unvaccinated and fully vaccinated groups, respectively. The unadjusted effectiveness against COVID-19 infection was 47% (95% CI 31–59%) whereas adjusted effectiveness was 39% (95% CI 20–64%). Interpretation: This real life study conducted in health care workers demonstrated that the effectiveness of two doses of the CoronaVac vaccine (39%) was lower than that determined in clinical trials. Due to reduce in protection over time or against variants, booster doses may be needed.